(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This article provides a doctrinal and systemic analysis of the legal and regulatory foundations governing tourism and recreational activities, conceptualizing tourism not as a purely economic sector but as a legally structured sphere of public interest regulation. The study proceeds from the assumption that tourism and recreation operate within a complex normative environment formed by the interaction of administrative law, land-use and zoning regulations, environmental protection legislation, and cultural heritage law, which collectively define the legal regime of recreational territories and tourism-related activities. Using an IMRaD-based analytical framework, the research identifies structural inconsistencies, normative fragmentation, and regulatory overlaps that hinder the effective governance of tourism and recreational development, particularly in areas of land allocation, environmental impact control, and institutional competence. Special attention is given to the hierarchical relationship between sector-specific tourism legislation and general regulatory instruments, demonstrating how the absence of legal coherence undermines sustainable tourism objectives. The article further examines the role of international legal instruments and soft-law standards in shaping national regulatory practices, highlighting the challenges of their domestic implementation. The findings substantiate that the sustainability and legal security of tourism and recreational activities depend not on the quantitative expansion of regulation, but on the internal consistency, enforceability, and functional integration of legal norms. The study contributes to legal scholarship by framing tourism and recreation as an integrated object of legal regulation and by proposing a conceptual basis for strengthening regulatory coherence in tourism governance.